A Fra-1-dependent, matrix metalloproteinase driven EGFR activation promotes human lung epithelial cell motility and invasion - Adiseshaiah, Pavan (2008)
We and others have shown a persistently high induction of Fra-1 transcription factor (a dimeric partner of AP-1) levels by respiratory carcinogens in pulmonary epithelial cells. Fra-1 is frequently overexpressed in various human tumors and cancer cells. We have recently shown that Fra-1 significantly promotes growth, motility, and invasion of human pulmonary epithelial cells, the precise molecular mechanisms by which this enhancement occurs are unclear. Because matrix metalloproteinases (MMPs) play key roles in wound healing and lung tumor metastasis, we tested the hypothesis that Fra-1 promotes lung epithelial cell motility and invasion via MMP activation. We show here that MMP-9 and MMP-2 activated signaling plays a critical role in regulating Fra-1-induced lung epithelial cell growth and invasion. Ectopic Fra-1 markedly stimulates MMP-2 and MMP-9 mRNA expression. Inhibition of MMP-2 and MMP-9 activity significantly attenuated Fra-1-driven cell motility and invasion. Furthermore, Fra-1 induced EGFR phosphorylation in an MMP-dependent manner, and an EGFR-specific inhibitor was able to block Fra-1-enhanced cell motility and invasion. Taken together, our data suggest that Fra-1 enhances lung cancer epithelial cell motility and invasion by inducing the activity of MMPs, in particular MMP-2 and MMP-9, and EGFR-activated signaling.